Hodgkin lymphoma novel management; A 20-year retrospective study - Farid Ghazizadeh; Mehran Noroozi; Amin Sedokani; Javad Rasouli; Amir Ebadpour (Journal of Preventive Epidemiology)
Introduction: Hodgkin lymphoma (HL) is one of the pediatric and adult cancers, with the treatment of chemotherapy alone or combined with radiotherapy. Objectives: We aimed to evaluate the consequences and outcomes of the treatment with or without radiotherapy in a retrospective study. Patients and Methods: We carried out a cross-sectional retrospective study by referring and reviewing records for all patients admitted to Motahari hospital with HL diagnosis from 1995 to 2016. The Ann Arbor staging system classified the staging of disease. Results: Totally, 35 patients enrolled in our study that 54.3% were female, and 45.7% were male patients. The mean age of patients was 10.08±6.38 years. 10 (28.6%) cases classified in stage 1, 13 (37.1%) case in stage 2, 9 (25.7%) cases in stage 3, and 3 (8.6%) cases in stage 4. 30 patients (85.7%) were treated by chemotherapy and 5 (14.3%) patients with chemotherapy and radiation combination. In our study, the overall survival was 97.1% of patients treated with chemotherapy alone, and one patient died due to drug side effects. That is comparable with other studies that treated patients with chemotherapy and radiotherapy. Conclusion: According to our findings, chemotherapy without radiotherapy as initial treatment in HL would have similar results to concomitant radiotherapy and chemotherapy, so considering the cost and harms of radiotherapy, we suggest a limitation of radiotherapy to patients with resistant diseases that do not respond to chemotherapy solo-protocols.